ENVIRONMENTAL COST OF MEAT CONSUMPTION: CROSS-COUNTRY ANALYSIS - Yergabulova, Aigerim (Nazarbayev University School of Sciences and Humanities, 2017)
Taxing meat consumption could be an important tool to mitigate negative effects of meat production on the environment (Wirsenius et al., 2011). Tax impact strongly depends on consumer preferences and household income. This paper is the first to predict the environmental implications of the introduction of meat consumption taxes in Eurasian Economic Union1 (EAEU) countries. Five meat products (beef, poultry, lamb, pork, and horse) and two greenhouse gases (methane and nitrous oxide) are included in this study that shows that the simultaneous introduction of taxes results in up to eleven percent of emissions reduction in livestock sector of EAEU countries.
Keywords: greenhouse gases; environmental tax; consumer preferences; demand analysis